2018
DOI: 10.1002/ardp.201800257
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis andin vitroanti-platelet aggregation activities of 2-methoxy-5-arylamido-N-(pyridin-3-yl-methyl)benzamides

Abstract: In order to discover novel compounds with anti-platelet aggregation activities, a series of novel 2-methoxy-5-arylamido-N-(pyridin-3-ylmethyl)benzamides (1a-n) were synthesized and their anti-platelet aggregation activities were evaluated by the turbidimetric method in response to the following agonists: adenosine diphosphate (ADP) (5 mM/L), arachidonic acid (AA) (20 µM/L), and collagen (1 mg/mL). Those synthesized compounds that have better in vitro activities were subjected to cell toxicity tests via cell co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Yoda1 was diluted to the final concentration of 25 μM (0.25% v/v DMSO). Previous studies revealed that 0.25% (v/v) DMSO showed neither obvious influences on ADP, collagen or thrombin induced platelets aggregation ( Yi et al, 2017 ; Wang et al, 2019 ) nor shear-induced platelet aggregation ( Supplementary Figure S1 ).…”
Section: Methodsmentioning
confidence: 89%
“…Yoda1 was diluted to the final concentration of 25 μM (0.25% v/v DMSO). Previous studies revealed that 0.25% (v/v) DMSO showed neither obvious influences on ADP, collagen or thrombin induced platelets aggregation ( Yi et al, 2017 ; Wang et al, 2019 ) nor shear-induced platelet aggregation ( Supplementary Figure S1 ).…”
Section: Methodsmentioning
confidence: 89%